A Short-Term Ketogenic Diet Impairs Markers of Bone Health in Response to Exercise - Heikura, Ida A.; Burke, Louise M.; Hawley, John A.; Ross, Megan L.; Garvican-Lewis, Laura; Sharma, Avish P.; McKay, Alannah K. A.; Leckey, Jill J.; Welvaert, Marijke; McCall, Lauren; Ackerman, Kathryn E. (Frontiers in Endocrinology, 2020)
Objectives: To investigate diet-exercise interactions related to bone markers in elite endurance athletes after a 3.5-week ketogenic low-carbohydrate, high-fat (LCHF) diet and subsequent restoration of carbohydrate (CHO) feeding. Methods: World-class race walkers (25 male, 5 female) completed 3.5-weeks of energy-matched (220 kJ·kg·d-1) high CHO (HCHO; 8.6 g·kg·d-1 CHO, 2.1 g·kg·d-1 protein, 1.2 g·kg·d-1 fat) or LCHF (0.5 g·kg·d-1 CHO, 2.1 g·kg·d-1 protein, 75-80% of energy from fat) diet followed by acute CHO restoration. Serum markers of bone breakdown (cross-linked C-terminal telopeptide of type I collagen, CTX), formation (procollagen 1 N-terminal propeptide , P1NP) and metabolism (osteocalcin, OC) were assessed at rest (fasting and 2 hr post meal) and after exercise (0 and 3 hr) at Baseline, after the 3.5-week intervention (Adaptation) and after acute CHO feeding (Restoration). Results: After Adaptation, LCHF increased fasting CTX concentrations above Baseline (p=0.007, Cohen’s d=0.69), while P1NP (p<0.001, d=0.99) and OC (p<0.001, d=1.39) levels decreased. Post-exercise, LCHF increased CTX concentrations above Baseline (p=0.001, d=1.67) and above HCHO (p<0.001, d=0.62), while P1NP (p<0.001, d=0.85) and OC concentrations decreased (p<0.001, d=0.99) during exercise. Exercise-related area under curve (AUC) for CTX was increased by LCHF after Adaptation (p=0.001, d=1.52), with decreases in P1NP (p<0.001, d=1.27) and OC (p<0.001, d=2.0). CHO restoration recovered post-exercise CTX and CTX exercise-related AUC, while concentrations and exercise-related AUC for P1NP and OC remained suppressed for LCHF (p=1.000 compared to Adaptation). Conclusion: Markers of bone modeling/remodeling were impaired after short-term LCHF diet, and only a marker of resorption recovered after acute CHO restoration. Long-term studies of the effects of LCHF on bone health are warranted.